PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION (STUDI PADA HOTEL RATU MAYANG GARDEN PEKANBARU) - Sitorus, Mardo Alnico Mangisi; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to analyze the effect of transformational leadership and organizational commitment toward turnover intention in Ratu Mayang Garden Hotel Pekanbaru. Transformational leadership as the first variable (X1), Organizational commitment as the second variable (X2), and turnover intention as the third variable (Y). The method in this research is descriptive and quantitative by using program of SPSS 21, where the sample used by 80 employees by census and technique of data collecting through questioner. The result of this analysis using test of validity, reliability test, determination, simple linear regression test, T test and F test so it can be concluded that transformational leadership have significant effect toward turnover intention, organizational commitment have significant effect toward turnover intention. Transformational leadership and organizational commitment have negative effect and significant toward turnover intention in Ratu Mayang Garden Hotel Pekanbaru. Keywords: transformational leadership, organizational commitment, and turnover intention